Phylogenomics and biogeography of the calamoid palms - Kuhnhäuser, BG (2021)
Tropical rainforests are the most diverse terrestrial biome, but their origins remain incompletely understood. Detailed analyses of the temporal and spatial context of the evolution of old and species-rich tropical rainforest lineages have potential to yield novel insights. However, only few such analyses are currently available.